2017
DOI: 10.1016/j.foreco.2017.07.039
|View full text |Cite
|
Sign up to set email alerts
|

Is silviculture able to enhance wild forest mushroom resources? Current knowledge and future perspectives

Abstract: Fungal fruit-bodies are an important economic resource both for recreational pickers and commercial markets. The broad interest in forest fungi and mushrooms has motivated attempts to develop appropriate silvicultural methods able to preserve and improve mushroom yields. Defining best practices for the sustainability and profitability of forest fungal resources is the main aim of 'mycosilviculture'. However, the difficulty of monitoring and studying such a cryptic kingdom (i.e., fungi) under real forest condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 99 publications
0
47
0
4
Order By: Relevance
“…Moreover, even low severity prescribed burning could have negative longlasting impacts on the ectomycorrhizal community (Taudi ere et al 2017). However, currently only a limited number of studies have assessed fire effects on mycorrhizae, hindering synthesis at the time of writing, but available evidence indicates a negative effect of elevated fire recurrence (Taudi ere et al 2017, Tomao et al 2017.…”
Section: Mycorrhyzal Networkmentioning
confidence: 99%
“…Moreover, even low severity prescribed burning could have negative longlasting impacts on the ectomycorrhizal community (Taudi ere et al 2017). However, currently only a limited number of studies have assessed fire effects on mycorrhizae, hindering synthesis at the time of writing, but available evidence indicates a negative effect of elevated fire recurrence (Taudi ere et al 2017, Tomao et al 2017.…”
Section: Mycorrhyzal Networkmentioning
confidence: 99%
“…The stand volume increment is peaking at the same time as the marketed mushroom yields of this study (Vuokila and Väliaho 1980). Similarly, it has been pointed out in several earlier studies that the yields of mycorrhizal mushrooms are high at the younger stands, where tree growth is also good (Senn-Irlet and Bieri 1999;Smith et al 2002;Bonet et al 2008;Egli et al 2010;Tomao et al 2017). Sporocarp production has also been found to be higher in young stands (20-30 years) in Finland (Hintikka 1988) and Estonia (Kalamees and Silver 1988).…”
Section: Biological Yields Of Marketed Mushroomsmentioning
confidence: 54%
“…The reactions of mushroom yields to thinnings on the other hand depend on numerous factors, e.g., thinning intensity, tree species composition and stand age (Tomao et al 2017). For example, in a study of Canadian Tsuga heterophylla and Thuja plicata stands, the response of ectomycorrhizal mushroom production after partial cuttings was studied, and the yields reacted differently depending on the stand structure and tree vigor after stand management operations (Kranabetter and Kroeger 2001).…”
Section: Forest Management and Production Of Marketed Mushroomsmentioning
confidence: 99%
“…The results of the present study are comparable with other studies investigating the effects of silvicultural systems on understory plant diversity, including species composition, structural attributes and functional organization. Studies demonstrated that, in general, the species pool was higher for selectively cut areas, and a high proportion of light reaching the forest floor induced the spread of light-demanding species and the detriment of true forest species [15,58].…”
Section: Discussionmentioning
confidence: 99%